Potential therapeutic effects of physical exercise for bipolar disorder - Sá Filho, Alberto Souza de (2015)
Cognitive deficits are observed in a variety of domains in patients with bipolar disorder (BD). These deficits are attributed to neurobiological, functional and structural brain factors, particularly in prefrontal cortex. Furthermore, cortical alterations in each phase (mania/hypomania, euthymia and depression) are also present. A growing basis of evidence supports aerobic exercise as an alternative treatment method for BD symptoms. Its benefits for physical health in healthy subjects and some psychiatric disorders are fairly established; however evidence directly addressed to BD is scant. Lack of methodological consistency, mainly related to exercise, makes it difficult accuracy and extrapolation of the results. Nevertheless, mechanisms related to BD physiopathology, such as hormonal and neurotransmitters alterations and mainly related to brain-derived neurotrophic factors (BDNF) can be explored. BDNF, specially, have a large influence on brain ability and its gene expression is highly responsive to aerobic exercise. Moreover, aerobic exercise trough BDNF may induce chronic stress suppression, commonly observed in patients with BD, and reduce deleterious effects caused by allostatic loads. Therefore, it is prudent to propose that aerobic exercise plays an important role in BD physiopathological mechanisms and it is a new way for the treatment for this and others psychiatric disorders.